MHD free convective heat transfer in fluids with oscillatory suction - Orukari, Mercy Amaebi; T Ngiangia, Alalibo (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
A study on the influence of Magnetohydrodynamic (MHD) flow of convective heat transfer in the presence of oscillatory suction velocity was carried out. Analysis of the solution governing the hydrodynamical equations showed that increase in Grashof number, angular frequency and Prandtl number correspond to an increase in velocity profile of the fluid while increase in magnetic Hartmann number results to a decrease in the velocity profile of the fluid. Increase in Prandtl number and angular frequency also caused a decrease in the temperature profile of the fluid.